2015
DOI: 10.1371/journal.pone.0125025
|View full text |Cite|
|
Sign up to set email alerts
|

Increasing Trends of Herpes Zoster in Australia

Abstract: BackgroundIncreasing trends in incidence of herpes zoster (HZ) have been reported in Australia and internationally. This may reflect the impact of childhood VZV vaccination programs introduced universally in Australia in late 2005. The objective of this study was to evaluate changes in incidence of HZ and PHN in Australia over time, and associated healthcare resource utilisation.MethodsAustralian data on general practice (GP) encounters for HZ, specific antiviral prescribing data from the pharmaceutical benefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 43 publications
4
52
1
Order By: Relevance
“…Unlike earlier national analyses (58,242), our hospitalisation findings suggested there is a small (in terms of absolute numbers), but significant increase in HZ admissions among 40-49 year olds, with the increase almost reaching significance among 60-69 year olds. Continued surveillance will be useful in identifying whether this trend will continue with the maturation of the VV program.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…Unlike earlier national analyses (58,242), our hospitalisation findings suggested there is a small (in terms of absolute numbers), but significant increase in HZ admissions among 40-49 year olds, with the increase almost reaching significance among 60-69 year olds. Continued surveillance will be useful in identifying whether this trend will continue with the maturation of the VV program.…”
Section: Resultscontrasting
confidence: 99%
“…In order to prevent HZ among those at high risk, the Australian Government has recently announced public funding for a live-attenuated zoster vaccine Reassuringly, an analysis of national data from Australia found age-standardised hospitalisations rates for HZ were lower in the first 4.5 years of the VV program compared to the 1.5 years immediately preceding vaccine licensure (58). Another recent study comparing age-specific Australian HZ hospitalisation rates up to 6.5 years post VV public funding found rates remained stable in all age-groups, except aged ≥80 years, in whom there had been a significant increase compared to the pre-vaccine funded period (242). Non-admitted patient data sources in Australia (242) and other countries (243-245) provide evidence of increasing HZ incidence rates more broadly across age-groups, however, they also show that the increasing trend preceded the VV programs, complicating the assessment of what role VV may have on increases in HZ rates (246).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 The majority of PHN cases occur in patients over 50 years of age. [4][5][6][7] The proportion of shingles patients who develop PHN increases with age (from approximately 1 in 10 cases in those aged 50-59 years to 1 in 4 cases in those aged over 80 years). 5,6,8 Other complications of shingles include:…”
Section: Complicationsmentioning
confidence: 99%
“…59 In conclusion, evidence of an increase of HZ in countries with a universal varicella vaccination program is not consistent; 60 many studies have shown evidence of increasing incidence trends in HZ in countries with or without a universal varicella vaccination program. 61,62,63 Besides, in some countries, HZ incidence started to increase years before the vaccine was introduced. For these reasons, continuous monitoring is needed to understand the secular trends in HZ before and after introduction of varicella vaccination programmes.…”
Section: Can Zoster Vaccine Be Co-administered To Other Vaccines?mentioning
confidence: 99%